2020
DOI: 10.1002/jcb.29672
|View full text |Cite
|
Sign up to set email alerts
|

Circ‐HOMER1 enhances the inhibition of miR‐1322 on CXCL6 to regulate the growth and aggressiveness of hepatocellular carcinoma cells

Abstract: Hepatocellular carcinoma (HCC) is a common liver malignancy worldwide accompanying with the high rate of recurrence. Accumulating reports have documented the significance of circular RNAs (circRNAs) in carcinogenesis and development of HCC. This study aimed to establish the mechanism underlying circ‐HOMER1 involvement in HCC. To this end, we identified a binding site for miR‐1322 via bioinformatics, quantitative reverse transcriptase‐polymerase chain reaction (qRT‐PCR), and dual‐luciferase reporter assays prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 38 publications
2
22
0
Order By: Relevance
“…30 A previous study suggested that circ_0006916 played an important role in HCC development. 15 In this study, we found that circ_0006916 could repress HCC development. Moreover, we were the first time to validate it was associated with circ_0006916/miR-599/SRSF2 network in HCC.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…30 A previous study suggested that circ_0006916 played an important role in HCC development. 15 In this study, we found that circ_0006916 could repress HCC development. Moreover, we were the first time to validate it was associated with circ_0006916/miR-599/SRSF2 network in HCC.…”
Section: Discussionmentioning
confidence: 60%
“…In this research, we found circ_0006916 abundance was elevated in HCC, which was also consistent with former reports. 14,15 Moreover, by treatment of RNase R and Actinomycin D, we found that circ_0006916 was stably expressed in HCC cells. To explore the potential role of circ_0006916, we performed the loss-of-function experiments, and found that circ_0006916 interference restrained HCC development via reducing cell viability, colony ability, migration and invasion and increasing cycle arrest and apoptosis, which was also like that in a previous report.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“… 40 In addition, Circ-HOMER1 enhances the inhibition of miR-1322 on CXCL6 to regulate the growth and aggressiveness of hepatocellular carcinoma. 41 We used a public prediction database to confirm that miR-1322 directly regulated CCL20 expression. Our results showed that the expression of miR-1322 was decreased in CRC patients, and F. nucleatum regulated the expression of CCL20 via miR-1322.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, hsa_circ_0003645 promoted cell migration, invasion and suppressed cell apoptosis ( 157 ). Circ-HOMER1 enhanced the proliferation, migration, invasion, and suppressed apoptosis ( 158 ). In addition, exosomal hsa_circ_0051443 enhanced cell apoptosis ( 159 ).…”
Section: Proliferative Metastasis and Apoptosismentioning
confidence: 99%